Gramscian Analysis of K-12 Schools in Brazil - Araujo, Alexandre Weingrill (Critical Education, 2023)
This paper aims at discussing the characteristics of the Brazilian K-12 educational system using contributions from the Italian scholar Antonio Gramsci. His writings about education discuss the effects of unequal distribution of educational opportunities among students of different social classes and the consequences of this inequality on the social fabric and human development. Using Gramsci’s contributions, this paper analyses empirical data about the public education system in Brazil and indicates that such a system is shaped for the maintenance of inequalities. Finally, it argues that the characteristics of the public schools in Brazil restrict the potential of intellectual and cultural development of pupils whom it serves.